(untitled) - Longenecker, Clinton O. (San Francisco, CA, 2007)
Uthors Clinton Longenecker, Greg Papp, and Timothy Stansfield reveal that all too often business organizations are defeated while the clock is still ticking. Bogged down by sluggish business practices that stifle change, they are unable to pick up the pace when necessary to score and win. The Two-Minute Drill translates football’s lessons for business leaders who want to succeed in today’s competitive marketplace. The book clearly shows what it takes to accelerate change and improvement within any type of organization.
Keywords: Organizational change,Organizational effectiveness,Organizational behavior,Sự thay đổi tổ chức,Hiệu quả của tổ chức,Tổ chức hành vi